Hubungan Sosial Warga Tua dengan Anak Dewasa: Kes Masyarakat Desa Kelantan (Jurnal Pembangunan Sosial, 2011)
Social relationship with children and relatives is very important for the life of older people. At old age, family is becoming increasingly important to the individuals as a place where they can find support. Indeed, social  relationship between older people with their adult children is particularly important to analyze. This paper is  intended to examine various aspects of the relationships, examined from the perspective of elderly parents.  Utilizing data from a face-to-face interview with 214 Malay rural residents in Kelantan aged 60 years and older, this study investigated patterns, frequency of visit, and quality of relationships between elderly parents and their adult children who live separately. Results revealed that adult children are important sources of social relationships; while nearly half of the adult children have frequently visited their elderly parents; and both elderly parents and their adult children perceived they were very important for each other.